THE USE OF FIGURATIVE LANGUAGE IN COPYWRITING OF TECHNOLOGY COMPANIES: Penggunaan Bahasa Kiasan pada Penulisan Iklan pada Perusahaan Teknologi - Najwa Khairunnisa Durrunnafis Soeparno; Aditya Nur Patria (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study aims to identify the types of figurative language used in the advertising copywriting of global technology companies and analyze its communicative function in conveying messages to the audience. The background of this study is based on the complexity of technology products, which are often difficult for the general public to understand, thus requiring a creative and persuasive communication approach. This study employs a descriptive qualitative method with text analysis techniques on 80 copywriting data from the top five technology companies according to Forbes in 2025, namely Apple, Microsoft, Nvidia, Amazon, and Alphabet. The analysis results indicate that metaphor, hyperbole, and personification are the most dominant types of figurative language used. The primary function of figurative language in technology advertising is to build an emotional connection with the audience, shape brand image, and simplify technical concepts. These findings confirm that figurative language not only enhances the message but also serves as an effective communication strategy to bridge the gap between technology products and consumers. This study is expected to serve as a reference for developing more humanistic and emotional marketing communication strategies in the digital age.